INDUKSI TUNAS IN VITRO DARI EKSPLAN TUNAS BUAH (SLIP) TANAMAN NANAS (Ananas comosus (L.) Merr.) ASAL KAMPAR DENGAN PENAMBAHAN 6-BENZYLAMINOPURINE (BAP) - Susiyani '; Wahyu Lestari; Siti Fatonah (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Pineapple (Ananas comosus (L.) Merr.) is widely cultivated. One of pineapple plantationcenters in Riau Province is the Kampar district. The vegetative seedling technique ofpineapple is done using tissue culture techniques. Pineapple plant part that used as explantsin this study is fruit buds. Explants were cut into whole bud and bud sectionedlongitudinally. The growth regulator used was BAP with different concentration, i.e. 0.0,0.5, 1.0, 1.5, 2.0, 2.5 mg/l in Murashige and Skoog (MS) medium. This study aims todetermine the optimum concentration of BAP as well as the best explant part and to get thebest combination between treatments in shoot induction. The study design used randomizedblock design (RBD) factorial. The concentration of 1.0 mg/l BAP on whole bud explantsinduced 3 buds, while the bud sectioned longitudinally induced only one shoot on control,and concentration at 0.5 and 1.0 mg/l. Whole bud explants induced shoots in all of thetreatments except the control. The interaction between treatment and the combination thatcould induced the greatest number of shoot was the whole bud explants with the additionof 1.0 mg/l BAP.